Mobilização de reservas e perfil preliminar de metabólitos secundários durante e após a germinação em Erythrina velutina - Silva, Diêgo Augusto Azevedo da (2020)
Considering the medicinal potential of Erythrina velutina Willd., a woody species native to the Caatinga, the aim of this work was to characterize the mobilization of reserves in parallel with the content secondary metabolites during seed germination and seedling establishment. Hence, seeds were scarified, surface-sterilized, planted between towel paper sheets and cultivated under controlled conditions. Then, seedlings were transferred to distilled water in hydroponics and cultivated in a greenhouse. In a time-course experiment, seedling growth, reserve mobilization and the content of soluble sugars and free amino acids, as well as the preliminary profile of secondary metabolites were assessed in the cotyledons during and after germination. Germination included the stages of imbibed seed and radicle protrusion, whereas establishment encompassed hypocotyl emergence, plumule hook opening, and the expansion of cordiform leaves, first trifoliate leaf and second trifoliate leaf. Seeds contained 20% starch, 14,5% storage proteins, 11,6% neutral lipids and 5,7% non-reducing sugars in dry weight basis. The major reserves were synchronically and intensely mobilized from apical hook opening, while non-reducing sugars were utilized from hypocotyl emergence. The activity of amylases, lipases and acid proteases increased from cordiform leaf emergence, coinciding with the mobilization of starch, lipids and proteins, respectively. By thin layer chromatography, it was possible to verify the presence of terpenes and phenolic acids during the experiment. The results indicate the occurrence of flavonoids from seed germination and at the expansion of cordiform leaves. Throughout the experiment, it was evidenced the presence of alkaloids, mainly in the imbibed seed. The elucidation of these processes may help in understanding the strategies used by E. velutina to colonize the environment as a Caatinga pioneer species.